A Inauspicious Month in Javanese Wedding Tradition in Luwu Utara, South Sulawesi: Perspective of Islamic Law - Rahmawati, Rahmawati; Takdir, Takdir; Muhajir, Muhammad Nur Alam; Abdain, Abdain (Universitas Islam Sultan Agung, 2024)
Determining inauspicious days in Javanese marriage traditions is significant. Sometimes, this leads to debates and controversies from various perspectives as it is considered contrary to Islamic law. This research aims to examine the determination of inauspicious days in Javanese marriage traditions during the month of Muharram (Suro). This study employs an empirical juridical approach using theories of social change and Islamic legal theory, particularly social tradition ('urf) and public interest (maslahah). Data is collected through interviews and literature reviews. Subsequently, the data is analyzed using these theories through data reduction, data presentation, and conclusion drawing processes. The research results reveal that the determination of inauspicious days in marriage traditions is based on the societal belief in the existence of inauspicious days for couples marrying in the month of Suro. This belief is grounded in experiences and stories passed down through generations. On the other hand, the concept of maslahah refers to the welfare or benefit for humans. In the context of inauspicious days for marriage, maslahah refers to efforts to prevent conflicts between couples and families. Furthermore, from the perspective of Islamic law, prohibiting marriage in the month of Suro in North Luwu Regency is permissible because there are no prohibitions in the Quran or hadith against it. Such traditions in Islamic law are referred to as ‘urf shahih, which are good and permissible customs as long as they do not contradict sharia. The prohibition is valid if it is based on the motivation to obey parental advice (birr al-walidayn) and as a form of respect for deceased parents, and linking everything that happens to the will of Allah SWT. However, if the tradition contradicts sharia and harms faith, then the tradition cannot be practiced.